Acoustic Radiation or Cavitation Forces From Therapeutic Ultrasound Generate Prostaglandins and Increase Mesenchymal Stromal Cell Homing to Murine Muscle - Lorsung, Rebecca M.; Rosenblatt, Robert B.; Cohen, Gadi; Frank, Joseph A.; Burks, Scott R. (Frontiers in Bioengineering and Biotechnology, 2020)
Nonablative ultrasound (US)-based techniques to improve targeted tropism of systemically-infused cell therapies, particularly mesenchymal stromal cell (MSC), have gained attention in recent years. Mechanotransduction following targeted US sonications have been shown to modulate tissue microenvironments by upregulating cytokines, chemokines, and trophic factors in addition to vascular cell adhesion molecules (CAM) that are necessary to promote tropism of MSC. While numerous US treatment parameters have demonstrated increased MSC homing, it remains unclear how the different mechanical US forces (i.e., acoustic radiation forces [ARF] or cavitation forces) influence tissue microenvironments. This study sonicated murine muscle tissue with pulsed focused ultrasound (pFUS) at 0.5 MHz or 1.15 MHz each over a range of US intensities. Following sonication, tissue was assayed for the prostaglandins (PG) PGH2 and PGE2 as indicators of microenvironmental changes that would support MSC tropism. PGH2 and PGE2 levels were correlated to physical pFUS parameters and acoustic emissions measured by hydrophone. While ARF (pFUS with absence of cavitation signatures) was sufficient to increase PGH2 and PGE2, nonlinear curve fitting revealed a frequency-independent relationship between prostaglandin production and mechanical index (MI), which accounts for increased cavitation probabilities of lower frequencies. The prostaglandin data suggested molecular changes in muscle would be particularly sensitive to cavitation. Therefore, low-intensity pulsed ultrasound (LIPUS) at 1 MHz was administered with low ARF (MI = 0.2) in combination with intravenous (IV) infusions of microbubble (MB) contrast agents. This combination upregulated prostaglandins and CAM without ultrasound-mediated microbubble destruction and ultimately promoted tropism of IV-infused MSC. This study revealed that accentuating nondestructive MB cavitation by US using parameters similar to diagnostic US contrast imaging increased MSC homing. Such approaches are particularly attractive to overcome clinical translation barriers of many still-experimental US parameters used in previous stem cell tropism studies.